Abstract 12896: ApoC3-Gln38Lys Variant is a Gain-of-function Mutation Associated With Human Hypertriglyceridemia - Yao, Zemin; Sundaram, Meenakshi; Curtis, Kaitlin R; Alipour, Mohsen A; Parks, Robin J; McIntyre, Adam D; Hegele, Robert A (Circulation (New York, N.Y.), 2016)
IntroductionCell culture and animal studies have suggested that expression of human apoC3 in liver cells can exert an intracellular role in promoting production of triglyceride (TG)-rich VLDL (VLDL1) under lipid-rich conditions. Previously, hypotriglyceridemia in human subjects have been linked to several loss-of-function apoC3 mutations, namely Ala23Thr and Lys58Glu. Conversely, hypertriglyceridemia has also been linked to an apoC3 variant. For example, the Gln38Lys variant was originally identified in human subjects of Mexican origin; heterozugous carriers of Gln38Lys exhibited moderate hypertriglyceridemia.HypothesisWe hypothesized that the Gln38Lys variant is a gain-of-function mutation that promotes hepatic VLDL assembly/secretion.MethodsThe recombinant Gln38Lys variant was either expressed in McA-RH7777 cells devoid of endogenous apoC3, or else expressed in apoc3-null mice using adenovirus-mediated gene transfer. The effect of Gln38Lys expression on hepatic lipogenesis, VLDL1 production, and glucose homeostasis was contrasted with that of wildtype apoC3.ResultsGln38Lys expression in McA-RH7777 cells and apoc3-null mice resulted in increased VLDL1-TG secretion, which was accompanied with increased de novo lipogenesis, increased adipogenesis, and severe hepatic steatosis (i.e. accumulation of TG and cholesteryl esters). Gln38Lys expression also increased glucose uptake and hepatic glycogen content, suggesting that apoC3 may play a role in hepatic glucose homeostasis. Live cell imaging revealed prominent association of apoC3 with endosomes, and the Gln38Lys-associated endosomes exhibited robust trafficking between Golgi apparatus and the cell periphery. Next generation sequencing of 1557 DNA samples from patients (of European, Chinese, African, and South Asian origins) with dyslipidemia (including hypertriglyceridemia, hypercholesterolemia and combined hyperlipidemia) did not detect Gln38Lys variant, nor was the Gln38Lys variant found in the ExAC databases containing 60,706 individuals.ConclusionsGln38Lys is a rare, gain-of-function variant that may stimulate TG-rich VLDL1 production under lipid-rich conditions, contributing to hypertriglyceridemia..